A Self-Defining "Bourgeoisie" in the Early French Revolution: The Milice Bourgeoise, the Bastille Days of 1789, and Their Aftermath. (March 2014) - Alpaugh, Micah
Abstract: Though recent scholars have argued that no self-defining " bourgeois " identities existed during the French Revolution, such perspectives do not consider the pivotal role Milice bourgeoise forces played in the Bastille insurrection and France's broader social upheavals of mid-1789. Combatting perceived lower-class disorder, explicitly " bourgeois " units composed of propertied citydwellers mobilized to seize control of and direct the central uprisings that made the Revolution. In Paris, the motley insurgents of July 12 were forcibly disarmed the next day by a militia hastily organized through the city's former Third Estate voting districts, which moved first against lower-class disorder instead of the royal forces menacing the city. Following the Bastille's fall, in municipal revolutions across France such units formed the basis for the new National Guard, which thereafter possessed exclusive policing rights. Based upon a wide reading of participant and observer accounts from the early Revolution, this article attempts to explain the role of socially exclusionary identities in motivating collective action in 1789. The French became revolutionary not through a unified uprising of "the people, " but rather under the aegis of a socially exclusive and self-definably " bourgeois " force.